The Influence of Labour Legislation on Job Creation and Job Sustainability in South Africa - Womack, Anna Johanna Catharina (AOSIS, 2020)
This scholarly book focuses on the issue of high unemployment and the challenges related thereto in South Africa. It demonstrates the urgent need for research into the contribution of job creation to poverty alleviation and economic growth. This research is relevant from a legal, economic and social sciences point of view. The main thesis of the book is to explore the influence of labour legislation on job creation. It investigates sustainability regarding employment relationships through the lens of the two primary participants: business and organised labour. This book adds value to the social justice context from both a societal and business point of view. It provides business and unionised labour a voice from which the influence of labour legislation on job creation and job sustainability can be addressed.